2006
DOI: 10.1111/j.1466-822x.2006.00265.x
|View full text |Cite
|
Sign up to set email alerts
|

Is the Rapoport effect widespread? Null models revisited

Abstract: Aim To test the Rapoport effect using null models and data sets taken from the literature. We propose an improvement on an existing method, testing the Rapoport effect in elevational and latitudinal distributions when distributions are restricted by sampling.Location Global.Methods First, we hypothesized that real range size distributions are similar to those expected by null assumptions (expected by only imposing boundaries to species distributions). When these distributions were different from those expected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(36 citation statements)
references
References 77 publications
1
34
0
1
Order By: Relevance
“…2005; Almeida‐Neto et al. 2006; Harcourt 2006; Kendall & Haedrich 2006; Morin & Chuine 2006; Ribas & Schoereder 2006). Other studies, however, have tended to refute the rule (Rohde et al.…”
Section: Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…2005; Almeida‐Neto et al. 2006; Harcourt 2006; Kendall & Haedrich 2006; Morin & Chuine 2006; Ribas & Schoereder 2006). Other studies, however, have tended to refute the rule (Rohde et al.…”
Section: Problemmentioning
confidence: 99%
“…1996; Kerr 1999; Fu et al. 2004; Bhattarai & Vetaas 2006; Kendall & Haedrich 2006; Ribas & Schoereder 2006; Stauffer & Rohde 2006).…”
Section: Problemunclassified
“…Using this method, he found that latitudinal range extent of marine and freshwater fishes is greatest at low (rather than high) latitudes, contrasting with Stevens (1989) who found no consistent Rapoport effect in marine environments (in accordance with his prediction that bathymetric variability gradients overlying latitudinal gradients would conceal the effect). Species with midpoints in the middle of an area, however, will have the largest possible range extents (Colwell and Hurtt 1994, Blackburn and Gaston 1996, Lyons and Willig 1997, Ribas and Schoereder 2006,Šizling et al 2009). In any given sampling area, endemic species with midpoints close to the boundaries of the predefined area are necessarily restricted to a small maximum potential latitudinal range extent, since they can by definition not extend farther in one direction from the midpoint than in the other and are therefore restricted in their range size by the geometric boundaries of the study area.…”
Section: Introductionmentioning
confidence: 99%
“…Some recent studies have addressed these statistical challenges by using randomization to compare results to appropriate null models (Lyons and Willig 1997, Diniz-Filho and Tôrres 2002, Ribas and Schoereder 2006, Beketov 2009, Davies et al 2011, Morin and Lechowicz 2011, Morin and Lechowicz 2013, by using more advanced grid-cell analyses over a two-dimensional landscape (Smith et al 1994, Meliadou and Troumbis 1997, Ruggiero et al 1998, Ruggiero and Hawkins 2006, Morin and Lechowicz 2011, Luo et al 2011, Whitton et al 2012, Morales-Castilla et al 2013, Morin and Lechowicz 2013 accounting for more complex climate patterns than simple latitudinal gradients, or by using quartile analyses to assess the impact of different groups of range sizes within the data set (e.g., by using only restricted-range species [Amend et al 2013, McCain and Knight 2013, Morin and Lechowicz 2013). However, evidence for Rapoport's Rule remains equivocal.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies dealt with possible biases in the data (Blackburn and Gaston 1996), demonstrating that the pattern is confined only to particular latitudes () and is not symmetric about the equator (Gaston and Chown 1999 a , ). Only a few studies have compared the observed patterns with null models, and not all were explicit about the assumed underlying mechanisms (, Lyons and Willig 1997, , Grytnes and Vetaas 2002, Arita 2005, Ribas and Schoereder 2006). Only ) and Gryntes and Vetaas (2002) considered possible trends in potential range sizes as factors affecting underlying mechanisms.…”
Section: Introductionmentioning
confidence: 99%